Radioterapia : papel actual en el cáncer de páncreas (2012)
ABSTRACT: Prognosis of pancreatic cancer is poor with a five-year survival rate of 5%-15% after radical treatment. Its silent but aggressive evolution and nonspecific manifestations delay diagnosis so that only 15%-20% of lesions can be resected when diagnosis is established. The remaining ones are not resectable because they have advanced locally or because metastases are already present. Therefore, different therapeutic approaches are required in order to improve the quality of life and, if possible, to lengthen survival. Chemotherapy and radiotherapy as sole treatments, or the combination of both, have not achieved satisfactory results. Presently, investigation is very active concerning therapy of locally advanced pancreatic cancer in order to find the best therapeutic protocol in terms of quality of life and survival.